Posttranslational Modifications of the Mineralocorticoid Receptor and Cardiovascular Aging - Gadasheva, Yekatarina; Nolze, Alexander; Grossmann, Claudia (Frontiers in Molecular Biosciences, 2021)
During aging, the cardiovascular system is especially prone to a decline in function and to life-expectancy limiting diseases. Cardiovascular aging is associated with increased arterial stiffness and vasoconstriction as well as left ventricular hypertrophy and reduced diastolic function. Pathological changes include endothelial dysfunction, atherosclerosis, fibrosis, hypertrophy, inflammation, and changes in micromilieu with increased production of reactive oxygen and nitrogen species. The renin-angiotensin-aldosterone-system is an important mediator of electrolyte and blood pressure homeostasis and a key contributor to pathological remodeling processes of the cardiovascular system. Its effects are partially conveyed by the mineralocorticoid receptor (MR), a ligand-dependent transcription factor, whose activity increases during aging and cardiovascular diseases without correlating changes of its ligand aldosterone. There is growing evidence that the MR can be enzymatically and non-enzymatically modified and that these modifications contribute to ligand-independent modulation of MR activity. Modifications reported so far include phosphorylation, acetylation, ubiquitination, sumoylation and changes induced by nitrosative and oxidative stress. This review focuses on the different posttranslational modifications of the MR, their impact on MR function and degradation and the possible implications for cardiovascular aging and diseases.